Preparation method of granular manganese lithium ion adsorbent and lithium ion adsorbent
Through impregnation co-precipitation and high-temperature calcination, a granular manganese lithium ion adsorbent was prepared, which solved the problems of poor powder flowability and insufficient stability, and achieved efficient lithium ion adsorption and stable industrial applications.
Patent Information
- Application Number
- CN202411618800.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-13
- Publication Date
- 2025-02-18
AI Technical Summary
The powder flowability of existing manganese-based adsorbents is poor, resulting in insufficient lithium extraction efficiency and poor stability, which is prone to blockage of mother liquor, which limits its industrial application.
By co-soluble lithium salt and manganese salt in water, adding a carrier molecular sieve, then adding a precipitant and complexing agent, impregnation and co-precipitation and high-temperature calcination, a granular manganese lithium ion adsorbent was prepared.
It improves the fluidity and stability of the adsorbent, enhances the adsorption capacity, reduces the manganese dissolution rate, and is suitable for industrial production and application.
Smart Images

Figure CN119455888A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium extraction adsorbents, and particularly relates to a preparation method of a granular manganese-based lithium ion adsorbent and the lithium ion adsorbent. Background Art
[0002] In recent years, with the rapid development of new energy industries, the demand for lithium has grown rapidly. The Qaidam Basin Salt Lake in Qinghai Province is the place where lithium resources are most densely distributed in my country. However, because the brine in the salt lake has a low lithium content and a high magnesium-lithium ratio, separation is difficult.
[0003] The main methods for extracting lithium from salt lake brine include precipitation, solvent extraction, calcination, electrodialysis, adsorption and membrane separation. When the precipitation lithium extraction process is used for salt lake brine with a high magnesium-lithium ratio, the precipitant consumption is large, the production cost is high, and it is not economical. Therefore, it is more suitable for lithium extraction from salt lake brine with a low magnesium-lithium ratio. Although the liquid-liquid extraction method has the characteristics of high extraction efficiency and excellent selectivity, the lithium extraction process causes serious corrosion to the equipment and is easy to dissolve during the stripping process. The production cost and environmental protection issues hinder the large-scale application of the process. The calcination lithium extraction process has high energy consumption, serious equipment corrosion, and a large amount of dilute hydrochloric acid is difficult to dispose of, which poses an environmental hazard. The electrodialysis lithium extraction process has a good magnesium-lithium separation effect, but a high magnesium-lithium ratio of the brine will reduce the recovery rate, thereby affecting the production cost. As for the adsorption method, it uses a specific adsorbent to extract lithium from brine through three steps of activation, adsorption and elution. It has the advantages of good selectivity, high recovery rate, safety and environmental protection. It is suitable for extracting lithium from brine with a high magnesium-lithium ratio in my country's salt lakes. It is one of the most promising lithium extraction technologies at present.
[0004] At present, manganese-based adsorbents have become widely used in industry for lithium extraction due to their advantages such as high lithium ion selectivity and low cost. 4 Mn 5 O 12 The main synthesis methods of powder can be divided into high temperature solid phase method and hydrothermal synthesis method. Zhang Guo-tai's research group synthesized Li by high temperature solid phase reaction. 1.6 Mn 1.6 O 4 , then Li 1.6 Mn 1.6 O 4 After pickling, MnO 2 0.5H 2 O. In Li + In a solution with a concentration of 350 mg / L, MnO 2 0.5H 2 The saturated adsorption capacity of O reached 29.87 mg / g, and Mn 2+The dissolution rate is 1.71%. Luo X's research group prepared Li 4 Mn 5 O 12 The precursor was eluted with hydrochloric acid to obtain a three-dimensional Li + Transport channel of MnO 2 Ion cage. Its maximum adsorption capacity for lithium can reach 56.87 mg / g. The powders obtained by the two methods are evenly distributed and have excellent adsorption effects. However, in terms of industrial application, there are problems such as poor powder fluidity and poor stability. In the process of column adsorption, it is easy to block the mother liquor, which is not conducive to industrial use.
[0005] In order to solve the defect of poor powder fluidity leading to insufficient lithium extraction efficiency and improve the stability of the adsorbent, many teams have adopted the method of adsorbent granulation and foaming to make up for the above shortcomings in recent years. Ma Li-wen's research group used asphalt as a binder and carrier through the foaming method to prepare a foamed manganese ion sieve. The ion sieve foam has a mesoporous / macroporous structure, allowing ions in the solution to pass freely. It shows a dynamic adsorption capacity of 3.83 mg / g and 1.49 mg / g in LiCl buffer solution and lithium-rich salt lake brine, respectively. Xiao Jia-li's research group used the reverse suspension polymerization method to use ammonium persulfate to initiate the polymerization of acrylamide to Li 4 Mn 5 O 12 Granulation was performed to obtain granular PAM-MnO 2 Ion sieve, the maximum equilibrium adsorption capacity of Li in lithium solution at 303K is 18.60mg / g, and the dynamic adsorption capacity is 4.30mg / g. After granulation modification, the flowability of the adsorbent is greatly increased, but the stability of the adsorbent is reduced, and powdering occurs after multiple cycles; at the same time, the overall adsorption capacity is reduced by 20%-30% on the original basis, which is also not conducive to long-term use by enterprises. Summary of the invention
[0006] In order to solve the problem of insufficient fluidity and poor stability of powdered manganese-based adsorbents, the present invention provides a method for preparing a granular manganese-based lithium ion adsorbent. The lithium ion adsorbent prepared by the method is granular and has high fluidity, which solves the problem of poor fluidity of powdered adsorbents in industrial applications and has excellent stability and adsorption capacity.
[0007] The invention also provides a granular manganese-based lithium ion adsorbent.
[0008] The present invention is achieved through the following technical solutions:
[0009] The present invention provides a method for preparing a granular manganese-based lithium ion adsorbent, the preparation method comprising:
[0010] Dissolving a lithium salt and a manganese salt in water to obtain a lithium-manganese solution, and adding a carrier molecular sieve to the lithium-manganese solution to obtain a mixed solution;
[0011] Adding a precipitant and a complexing agent to the mixed solution, stirring and reacting for a certain period of time to obtain a reaction solution;
[0012] The reaction solution is aged, and then solid-liquid separation is performed, and the obtained precipitate is dried to obtain a coprecipitation carrier;
[0013] The coprecipitated carrier is calcined at high temperature to obtain a manganese-based lithium ion adsorbent.
[0014] Furthermore, the lithium salt includes lithium sulfate monohydrate, the manganese salt includes manganese sulfate monohydrate, the molar ratio of the lithium salt to the manganese salt is (1-1.5):1, and the total concentration of the lithium manganese solution is 1.3-1.7 mol / L.
[0015] Preferably, the molar ratio of the lithium salt to the manganese salt is 1.3:1, and the total concentration of the lithium manganese solution is 1.5 mol / L.
[0016] Furthermore, the carrier molecular sieve includes any one of activated alumina, 3A potassium molecular sieve, 4A sodium molecular sieve, 5A calcium molecular sieve and 13X sodium molecular sieve, and the carrier molecular sieve is spherical in shape and has a particle size of 1 to 2 mm.
[0017] Preferably, the carrier molecular sieve is activated alumina.
[0018] Furthermore, the adding of carrier molecular sieve into the lithium manganese solution to obtain a mixed solution specifically comprises:
[0019] At 70-100° C., immersing the carrier molecular sieve in the lithium manganese solution for 20-30 minutes to obtain a mixed solution;
[0020] Wherein, the ratio of the mass of the carrier molecular sieve to the volume of the lithium manganese solution is 6g:25ml.
[0021] Preferably, the immersion temperature of the carrier molecular sieve in the lithium manganese solution is 90° C. and the immersion time is 30 min.
[0022] Further, the adding of a precipitant and a complexing agent into the mixed solution, stirring and reacting for a certain period of time to obtain a reaction solution specifically comprises:
[0023] Add the precipitant and the complexing agent to the mixed solution at 70-100° C. at a rate of 5-10 rpm, stirring during the addition process, and continue stirring for 50-60 minutes after the addition is completed to obtain a reaction solution.
[0024] Preferably, the stirring rate is 400-600 r / min, more preferably 500 r / min; the feeding rate is 7.5 rpm, and the reaction temperature is 90°C.
[0025] Further, the precipitant comprises a sodium carbonate solution, wherein the molar ratio of the sodium carbonate solution to the lithium manganese solution reaction substance is 1:(0.5-2);
[0026] The complexing agent is ammonia water, the concentration of the ammonia water is 1-5 mol / L, and the volume ratio of the ammonia water to the lithium manganese solution is 1:1.
[0027] Preferably, the concentration of the aqueous ammonia is 2 mol / L.
[0028] Furthermore, the reaction solution is aged, solid-liquid separation is performed, and the obtained precipitate is dried to obtain the coprecipitation carrier, which specifically includes:
[0029] The reaction solution is aged at 75-95° C. for 1-4 hours, and then solid-liquid separation is performed. The obtained precipitate is dried at 80-90° C. to obtain a coprecipitation carrier.
[0030] Preferably, the reaction solution is aged at 90°C for 2h and the drying temperature is 80°C.
[0031] Furthermore, the coprecipitated carrier is subjected to high temperature calcination to obtain a manganese-based lithium ion adsorbent, which specifically includes:
[0032] The coprecipitated carrier is calcined at 400-600° C. for 8-12 hours, and then the powder is filtered off to obtain a manganese-based lithium ion adsorbent.
[0033] Preferably, the calcination temperature is 500° C. and the calcination time is 10 h.
[0034] Based on the same inventive concept, the present invention provides a granular manganese-based lithium ion adsorbent, which is prepared by the above-mentioned preparation method of a granular manganese-based lithium ion adsorbent.
[0035] Based on the same inventive concept, the present invention also provides an application of a granular manganese-based lithium ion adsorbent in lithium extraction from salt lake brine.
[0036] Preferably, the salt lake brine is Qarhan Salt Lake brine.
[0037] One or more technical solutions in the embodiments of the present invention have at least the following technical effects or advantages:
[0038] 1. The present invention discloses a method for preparing a granular manganese-based lithium ion adsorbent. The method utilizes the structure of a carrier molecular sieve with high specific surface area and pore volume, and deposits the adsorbent on the surface and inside of the carrier molecular sieve by impregnation co-precipitation and high-temperature calcination. The adsorbent is further stably loaded and deposited on the surface and inside of the carrier molecular sieve by high-temperature calcination. The final product is in granular form and has the advantages of high fluidity and large adsorption capacity. Compared with the current industrial foaming method and sol-gel granulation method, the method has the advantages of higher stability and lower manganese dissolution rate.
[0039] 2. The present invention discloses a method for preparing a granular manganese-based lithium ion adsorbent. Through the method of impregnation co-precipitation and high-temperature calcination, the synthesized manganese-based adsorbent can be stably fixed on the surface and inside of the carrier particles. On the one hand, the mechanical strength and stability of the adsorbent are improved. On the other hand, the method has the advantages of reducing production costs, simple operation, low energy consumption, and stable effluent. The method is scientific, simple and easy to operate, and the preparation process is easy to control. Only impregnation co-precipitation reaction and high-temperature calcination are required to form the desired adsorbent. No expensive equipment and precious metals are required as reaction conditions. At the same time, the carrier molecular sieve and raw materials are widely available, the cost is low, and it is suitable for mass production.
[0040] 3. The present invention discloses a granular manganese-based lithium ion adsorbent, which has the advantages of fast adsorption rate of lithium ions, high adsorption capacity and stable adsorption performance. The calcined granular manganese-based lithium ion adsorbent is placed in a hydrochloric acid solution for acid leaching activation, and the lithium ions in the precursor lithium manganate are exchanged with the hydrogen ions in the hydrochloric acid solution to form an ion sieve with a lithium ion memory effect. The ion sieve is then applied to a salt lake to exchange lithium ions again, thereby achieving the purpose of adsorption. The ion sieve can be applied to lithium extraction from salt lake brine with a magnesium-to-lithium mass ratio (Mg / Li) of 100. The manganese-based lithium ion adsorbent exhibits very good low manganese dissolution performance during the acidification and adsorption processes. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0042] Figure 1 The present invention is a flow chart of the preparation process and application of the granular manganese-based lithium ion adsorbent;
[0043] Figure 2 This is the XRD diagram of the granular manganese-based lithium ion adsorbent of Example 1 of the present invention;
[0044] Figure 3This is a SEM image of the granular manganese-based lithium ion adsorbent of Example 1 of the present invention;
[0045] Figure 4 This is a BET diagram of the granular manganese-based lithium ion adsorbent of Example 1 of the present invention;
[0046] Figure 5 This is a FTIR diagram of the granular manganese-based lithium ion adsorbent of Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The present invention will be described in detail below in conjunction with specific implementations and examples, and the advantages and various effects of the present invention will be more clearly presented. It should be understood by those skilled in the art that these specific implementations and examples are used to illustrate the present invention, rather than to limit the present invention.
[0048] Throughout the specification, unless otherwise specifically stated, the terms used herein should be understood as meanings commonly used in the art. Therefore, unless otherwise defined, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. In the event of a conflict, the present specification takes precedence.
[0049] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.
[0050] The technical principle of the present invention is as follows:
[0051] In view of the shortcomings of the prior art, the present invention provides a method for preparing a granular manganese-based lithium ion adsorbent. On the one hand, the high fluidity of the spherical carrier solves the problem of poor fluidity of powdered adsorbents in industrial applications. On the other hand, under the premise of ensuring the fluidity of the adsorbent, the adsorbent can be firmly loaded on the carrier through high-temperature calcination, thereby improving the stability. At the same time, the adsorbent can be loaded on the surface of the carrier and inside the pore volume to achieve the purpose of fast adsorption rate and high adsorption capacity.
[0052] The present invention provides a method for preparing a granular manganese-based lithium ion adsorbent, the preparation method comprising:
[0053] S1. dissolving a lithium salt and a manganese salt in water to obtain a lithium manganese solution, and adding a carrier molecular sieve to the lithium manganese solution to obtain a mixed solution;
[0054] S2. Add a precipitant and a complexing agent to the mixed solution, stir the reaction for a certain time to obtain a reaction solution;
[0055] S3. The reaction solution is aged, and then solid-liquid separation is performed, and the resulting precipitate is dried to obtain a coprecipitation carrier;
[0056] S4. The coprecipitated carrier is calcined at high temperature to obtain a manganese-based lithium ion adsorbent.
[0057] In step S1, the lithium salt includes lithium sulfate monohydrate, the manganese salt includes manganese sulfate monohydrate, the molar ratio of the lithium salt to the manganese salt is (1-1.5):1, and the total concentration of the lithium manganese solution is 1.3-1.7 mol / L.
[0058] In the present invention, the molar ratio of lithium salt to manganese salt is (1-1.5):1, and a precursor powder meeting the lithium-manganese ratio can be synthesized. A molar ratio that is too low or too high will result in an unreasonable lithium-manganese ratio in the precursor solution, which will in turn lead to the failure to form lithium manganate in the later stage. The total concentration of the lithium-manganese solution is 1.3-1.7 mol / L, which is convenient for preparing the lithium-manganese stock solution.
[0059] Furthermore, the carrier molecular sieve includes any one of activated alumina, 3A potassium molecular sieve, 4A sodium molecular sieve, 5A calcium molecular sieve and 13X sodium molecular sieve, and the carrier molecular sieve is spherical in shape and has a particle size of 1 to 2 mm.
[0060] In the present invention, the carrier molecular sieve adopts activated alumina, 3A potassium molecular sieve, 4A sodium molecular sieve, 5A calcium molecular sieve or 13X sodium molecular sieve. The advantage is that the above molecular sieves are all granular, which can improve the fluidity, and have a pore volume that can load a certain amount of adsorbent on the surface and inside of the particles. The advantage of the carrier molecular sieve having a particle size of 1 to 2 mm is that the particle specific surface area and pore volume can load the largest amount of adsorbent (specifically 22% of the mass of the molecular sieve).
[0061] Furthermore, the adding of carrier molecular sieve into the lithium manganese solution to obtain a mixed solution specifically comprises:
[0062] At 70-100° C., immersing the carrier molecular sieve in the lithium manganese solution for 20-30 minutes until the pores of the carrier molecular sieve in the lithium manganese solution are saturated without bubbles, thereby obtaining a mixed solution;
[0063] Wherein, the mass concentration of the carrier molecular sieve in the mixed solution is 1.5 to 2 mol / L.
[0064] In the present invention, the purpose of impregnating the carrier molecular sieve in the lithium manganese solution is to saturate the internal pore volume of the carrier molecular sieve so that a co-precipitation can be formed later. The impregnation temperature is 70-100° C. On the one hand, the impregnation rate increases with the increase of temperature, and the pore volume can reach saturation faster; on the other hand, the solubility of lithium carbonate decreases with the increase of temperature. Therefore, the higher the impregnation temperature, the faster the generation of lithium carbonate and manganese carbonate after the subsequent addition of a precipitant, thereby increasing the reaction rate.
[0065] Step S2 specifically includes:
[0066] Add the precipitant and the complexing agent to the mixed solution at 70-100° C. at a rate of 5-10 rpm, stirring during the addition process, and continue stirring for 50-60 minutes after the addition is completed to obtain a reaction solution.
[0067] In the present invention, the purpose of adding the precipitant and the complexing agent to the mixed solution is that the addition of the precipitant can cause the anions in the precipitant to undergo a double decomposition reaction with the cations in the mother solution, thereby forming a lithium carbonate manganese carbonate coprecipitation. Through the complexing action of the complexing agent, the disturbance of the coprecipitation equilibrium caused by the addition of the precipitant can be slowed down, which can not only control the supersaturation of the precipitate in the stock solution, but also reduce the nucleation and growth rate of lithium carbonate manganese carbonate crystals; at the same time, the addition of the complexing agent can avoid the nucleation of lithium carbonate manganese carbonate alone, so that the overall structure becomes compact and uniform. The advantage of the feed rate of 5 to 10 rpm is that the supersaturation of the solution can be regulated. According to the principle that the solubility of lithium carbonate continuously decreases with the increase of temperature, the reaction temperature is 70-100°C, which can precipitate lithium carbonate and manganese carbonate that meet the standard lithium manganese ratio.
[0068] Further, the precipitant comprises a sodium carbonate solution, wherein the molar ratio of the sodium carbonate solution to the lithium manganese solution reaction substances is 1:(0.5-2) (i.e.: carbonate ion: manganese ion: lithium ion (molar ratio) = 1:1:2);
[0069] The complexing agent is ammonia water, the concentration of the ammonia water is 1-5 mol / L, and the volume ratio of the ammonia water to the mixed liquid is 1:1.
[0070] In the present invention, the precipitant adopts sodium carbonate solution, which has the advantages that sodium carbonate as an inorganic coprecipitant is more environmentally friendly and safer than an organic coprecipitant, and carbonate ions in sodium carbonate can form manganese carbonate and lithium carbonate with lithium ions and manganese ions, and the two can smoothly form a coprecipitation meeting the standard lithium-manganese ratio at a certain water bath temperature, and sodium carbonate is economical and suitable for mass production in industry. The reaction ratio of sodium carbonate to lithium-manganese solution is 1: (0.5-2), which has the advantage that carbonate ions can react with lithium ions and manganese ions in the mother liquor just at the reaction ratio, thereby forming a coprecipitation corresponding to the lithium-manganese ratio. If the reaction ratio is less than the reaction ratio, the precipitation is incomplete, and if the reaction ratio is more, it causes waste.
[0071] Step S3 specifically includes:
[0072] The reaction solution is aged at 75-95° C. for 1-4 hours, at which time the lithium-manganese ratio in the coprecipitate is 0.468-1.013, and then solid-liquid separation is performed. The obtained precipitate is dried at 80-90° C. to obtain a coprecipitation carrier.
[0073] In the present invention, the aging temperature is 75-95°C and the aging time is 1-4h. The advantage is that the supersaturation in the solution can be reduced by aging, and the MnSO in the lithium carbonate manganese carbonate solid can be solved. 4 The problem of crystal inclusion, the advantage of the lithium manganese ratio in the coprecipitate being 0.468-1.013 is that it satisfies the final formation of lithium manganate Li 4 Mn 5 O 12 The lithium-manganese ratio is 0.8, and the precipitate is dried at 80-90°C to accelerate the evaporation of water.
[0074] Preferably, the insulation temperature is 90° C., the aging time is 2 h, and the lithium-manganese ratio is 0.853.
[0075] In the present invention, the filter screen used for solid-liquid separation has a specification of 16 meshes.
[0076] Step S4 specifically includes:
[0077] The coprecipitated carrier is calcined at 400-600° C. for 8-12 hours, and then the powder is filtered off to obtain a manganese-based lithium ion adsorbent.
[0078] In the present invention, the calcination temperature of the coprecipitated carrier is 400-600°C, which has the advantage of forming lithium manganate with a regular octahedral spinel structure. If the calcination temperature is too low, the manganese carbonate is not completely decomposed at high temperature and cannot be completely decomposed into manganese trioxide (Mn 2 O 3 ), so when it reacts with lithium carbonate, only a small amount of manganese trioxide will react with lithium carbonate to form lithium manganate Li 4 Mn 5 O 12 , and the rest are manganese oxides; on the other hand, if the temperature is too low, the adsorbent on the surface of the carrier molecular sieve is not firm, and a large amount of powder will fall off during use; if the roasting temperature is too high, manganese carbonate will further generate impurities such as manganese tetraoxide (Mn 3 O 4 ), while the reaction of trimanganese tetroxide with lithium carbonate will generate Li 2 MnO3, this lithium manganate is reddish brown in color and has a stable structure, but does not have adsorption properties. The calcination time is 8 to 12 hours. If the calcination time is too short, manganese carbonate is not completely oxidized and cannot react with lithium carbonate to form spinel lithium manganate; if the calcination time is too long, it will affect the progress of the experiment.
[0079] In the present invention, the filter screen used to filter out the powder has a specification of 16 meshes.
[0080] The preparation method of a granular manganese-based lithium ion adsorbent and the lithium ion adsorbent of the present application will be described in detail below in combination with examples and experimental data.
[0081] The activated alumina carrier particles and different types of molecular sieves used in the following examples were purchased from Henan Lvxinyuan Environmental Protection Filter Material Factory.
[0082] Example 1
[0083] The method for preparing a granular manganese-based lithium ion adsorbent in this embodiment specifically comprises the following steps:
[0084] (a) Impregnation: Manganese sulfate monohydrate and lithium sulfate monohydrate are dissolved in water according to different lithium manganese raw material ratios to prepare 250 ml of 1.5 mol / L lithium manganese solution; 50 g of active alumina carrier (spherical particles with a particle size of 1-2 mm) is added to the prepared lithium manganese solution, and impregnation is carried out at a water bath temperature of 90° C. for 30 min;
[0085] (b) Coprecipitation reaction: a precipitant (2.438 mol / L sodium carbonate solution) and a 2 mol / L ammonia solution were added dropwise to the solution in step (a) at a feeding rate of 7.5 rpm (12 ml / min), and a dynamic stirring rate of 500 r / min was performed at a temperature of 90° C. After the addition of the sodium carbonate solution and the ammonia solution was completed (250 ml of each was added), stirring was continued for 60 min until the reaction was completed;
[0086] (c) Aging: After the reaction in step (b) is completed, the mixture is heated in a water bath at 90° C. and aged for 2 h;
[0087] (d) Filtration and drying: The aged coprecipitate was filtered through a 16-mesh filter screen to filter out the water to obtain the coprecipitation carrier, and then placed in an oven at 80° C. and dried for 2 h;
[0088] (e) High temperature calcination: The dried coprecipitated carrier obtained in step (d) was placed in a nickel crucible and calcined at 500°C for 10 hours, and then the powder was filtered out through a 16-mesh sieve to obtain a granular manganese-based lithium ion adsorbent. Table 1 below lists the prepared adsorbents with three different lithium-manganese raw material ratios.
[0089] Table 1
[0090]
[0091]
[0092] Example 2
[0093] The method for preparing a granular manganese-based lithium ion adsorbent in this embodiment specifically comprises the following steps:
[0094] (a) Impregnation: dissolve monohydrate manganese sulfate and monohydrate lithium sulfate raw materials in water at a ratio of 1.3:1 to prepare 250 ml of 1.5 mol / L lithium manganese solution; add 50 g of activated alumina support to the prepared solution, and impregnate at 90°C water bath temperature for 30 min;
[0095] (b) coprecipitation reaction: 250 ml of a 2.438 mol / L precipitant sodium carbonate solution and an ammonia solution were added dropwise to the solution in step (a) at a feeding rate of 7.5 rpm (12 ml / min), and the mixture was stirred at a rate of 500 r / min at a temperature of 90° C. After the addition of the sodium carbonate solution and the ammonia solution was completed, stirring was continued for 60 min until the reaction was completed;
[0096] (c) Aging: After the reaction in step (b) is completed, the mixture is heated in a water bath at 90° C. and aged for 2 h;
[0097] (d) Filtration and drying: The aged coprecipitate was filtered through a 16-mesh filter screen to filter out water to obtain a coprecipitation carrier, which was then placed in an oven at 80° C. and dried for 2 h;
[0098] (e) High temperature calcination: The dried coprecipitated support obtained in step (d) was placed in a nickel crucible and calcined at 500°C for 10 hours, and then the powder was filtered out through a 16-mesh sieve to obtain a granular manganese-based lithium ion adsorbent. Table 2 below lists the two adsorbents prepared with and without the addition of an ammonia complexing agent.
[0099] Table 2
[0100] Granular manganese adsorbent Whether to add ammonia complexing agent 1 Add 2mol / L250ml ammonia water 2 No ammonia added
[0101] Example 3
[0102] The method for preparing a granular manganese-based lithium ion adsorbent in this embodiment specifically comprises the following steps:
[0103] (a) Impregnation: dissolve monohydrate manganese sulfate and monohydrate lithium sulfate raw materials in water at a ratio of 1.3:1 to prepare 250 ml of 1.5 mol / L lithium manganese solution; add 50 g of activated alumina support to the prepared solution, and impregnate at 90°C water bath temperature for 30 min;
[0104] (b) coprecipitation reaction: 2.438 mol / L of sodium carbonate solution and 2 mol / L of ammonia solution as a precipitant were added dropwise to the solution in step (a) at a feeding rate of 7.5 rpm (12 ml / min), and the mixture was stirred at a rate of 500 r / min at a temperature of 90° C. After the addition of 250 ml of sodium carbonate solution and 250 ml of ammonia solution was completed, stirring was continued for 60 min until the reaction was completed;
[0105] (c) Aging: After the reaction in step (b) is completed, the mixture is heated in a water bath at 90° C. and aged for 2 h;
[0106] (d) Filtration and drying: The aged coprecipitate was filtered through a 16-mesh filter screen to filter out the water to obtain the coprecipitation carrier, and then placed in an oven at 80° C. and dried for 2 h;
[0107] (e) High temperature calcination: The dried coprecipitated support obtained in step (d) was placed in a nickel crucible and calcined at different temperatures for 10 hours, and then the powder was filtered out through a 16-mesh sieve to obtain a granular manganese-based lithium ion adsorbent. Table 3 below lists the adsorbents prepared at three different calcination temperatures.
[0108] Table 3
[0109] Adsorbent Different calcination temperatures (℃) 1 400 2 500 3 600
[0110] Example 4
[0111] In this example, the adsorption performance of the adsorbent prepared in Examples 1-3 was tested.
[0112] 1) In order to determine the excellent adsorption and desorption performance of the granular manganese-based lithium ion adsorbent synthesized under different synthesis conditions, HCl with a volume of 1.7L and a concentration of 0.05mol / L was passed from bottom to top into a column chromatography column containing the granular manganese-based lithium ion adsorbent at a certain flow rate, and the outlet liquid was collected in a beaker. After the hydrochloric acid was added, the activated manganese-based lithium extraction adsorbent was obtained. Then, the Li in the effluent was detected by inductively coupled plasma. + The concentration of is used to calculate the activation rate of the adsorbent.
[0113] 2) Distilled water flows through the adsorption column from bottom to top at a certain flow rate. After washing, the outflowing liquid Li is detected by inductively coupled plasma. + It approaches to 0, and the pH of the effluent is detected to be close to 7, indicating that the adsorbent has been cleaned.
[0114] 3) At room temperature, prepare a solution with a lithium ion concentration of 100 mg / L, a magnesium ion concentration of 10 g / L, and a pH of 9 as a mother solution. Pass 3 L of the mother solution from bottom to top at a flow rate of 4 rpm into a column chromatography column filled with a granular manganese adsorbent, and take samples with a sampling bottle every 20 minutes (e.g. Figure 1 ). Then, the Li in the sample solution was detected by inductively coupled plasma. + The concentration of the adsorbent is used to calculate the adsorption rate, dynamic adsorption capacity and saturated adsorption capacity of the adsorbent.
[0115] 4) After the granular manganese adsorbent is adsorbed, there is still a mother liquid of the adsorption bed volume in the column chromatography column. This part of the mother liquid needs to be washed out with distilled water to avoid interference with subsequent desorption. Distilled water is passed through the adsorption column from bottom to top at a certain flow rate. After washing, the outflowing liquid Li is detected by inductively coupled plasma. + When it approaches 0, it means that the adsorbent has been cleaned.
[0116] 5) To obtain the Li adsorbed in the adsorbent + Similarly, 1.7 L of HCl with a concentration of 0.05 mol / L was passed from bottom to top into the column chromatography column at a flow rate of 5 rpm for desorption. After desorption was completed, the effluent Li was analyzed by inductively coupled plasma. + and Mn 2+ Concentration, calculate Li + Desorption rate and Mn 2+ Dissolution rate.
[0117] Table 4 Application data of granular manganese lithium ion adsorbent corresponding to different raw material ratios in Example 1
[0118]
[0119] In Table 4, the calculation formula for the adsorbent loading rate is: (m 后 -m 前 ) / m 前 *100%, where m 后 Represents the mass of the carrier after loading, m 前 Represents the mass of the carrier before loading.
[0120] Table 5 Application data of granular manganese lithium ion adsorbent corresponding to whether ammonia complexing agent is added in Example 2
[0121]
[0122] Table 6 Application data of granular manganese lithium ion adsorbent corresponding to different calcination temperatures in Example 3
[0123] Different calcination temperatures (℃) Activation rate (%) Adsorption rate (%) 400 99.617 76.751 500 98.915 94.043 600 98.843 67.786 Dynamic adsorption capacity (mg / g) Desorption rate (%) Manganese dissolution rate (%) 1.910 97.940 0.218 2.122 90.023 0.043 1.687 94.609 0.167
[0124] It can be seen from the results in Table 4 that when the lithium manganese raw material ratio is 1.3:1, the lithium manganese ratio in the solution is 0.802, which is closer to Li compared with the lithium manganese raw material ratios of 1.1:1 and 1.5:1. 4 Mn 5 O 12 The lithium-manganese ratio in lithium manganate is 0.8. At the same time, the adsorption performance of the adsorbent corresponding to the lithium-manganese raw material ratio of 1.3:1 is also significantly better than the adsorption performance of the adsorbent corresponding to the lithium-manganese raw material ratio of 1.1:1 and 1.5:1.
[0125] It can be seen from the results in Table 5 that the adsorbent synthesized after adding ammonia water is significantly better than the adsorbent synthesized without adding ammonia water in terms of stability.
[0126] It can be seen from the results in Table 6 that the adsorption performance of the adsorbent synthesized at a calcination temperature of 500°C is also better than that of the adsorbents synthesized at calcination temperatures of 400°C and 600°C.
[0127] The adsorbent synthesized under this condition was tested for its saturated adsorption capacity. When the concentration of the effluent from the chromatography column was equal to the concentration of the mother liquor, it was determined that the adsorption had reached saturation. At this time, the saturated adsorption capacity of the adsorbent was calculated to be 4.932 mg / g.
[0128] Figure 2 The XRD pattern of the granular manganese-based lithium ion adsorbent (lithium-manganese raw material ratio 1.3:1) in Example 1: The prepared lithium manganate product was analyzed by X-ray diffractometer (BTX III, Olympus), and compared with the standard spectrum to determine the composition. The instrument parameters were uniformly set to: 40KV scanning voltage, 0.02° step width, 2° / min scanning speed, 30mA current, and 10°-80° scanning range.
[0129] from Figure 2 It can be seen that when the raw material ratio is 1.3:1, the hk l characteristic peaks of (111), (311), (222), (400), (311), (511), (440) and (531) in the formed precursor all show 8 characteristic peaks, which can be compared with Li with Fd-3m space group (JCPDS card number 46-0810). 4 Mn 5 O 12 The cubic spinel structure of the adsorbent is associated with that of the lithium manganate adsorbent. It is proved that the adsorbent synthesized by the impregnation co-precipitation method and high temperature calcination method is a lithium manganate adsorbent.
[0130] Figure 3 The SEM image of the granular manganese-based lithium ion adsorbent (lithium-manganese raw material ratio 1.3:1) of Example 1 of the present invention is as follows: the particle size and crystal appearance of the powder adsorbent before and after adsorption were observed using a scanning electron microscope (HI TACHI SU8010, Hitachi). The working parameters of the instrument are: the instrument magnification is 5k-10w times, the accelerating electrode voltage is set to 15KV, and the resolution is 10μm.
[0131] from Figure 3 It can be seen that when the raw material ratio is 1.3:1 and the lithium-manganese ratio is 0.802, according to Figure 3The enlarged image shows that the crystal structure formed is a regular octahedral spinel structure. This proves that the lithium manganate adsorbent synthesized by the impregnation co-precipitation method and high-temperature calcination method is a spinel structure.
[0132] Figure 4 The BET diagram of the granular manganese-based lithium ion adsorbent of Example 1 of the present invention: The specific surface area and pore size structure of the adsorbent were investigated using a specific surface area and pore size analyzer (ASAP2460, Micromeritics) to determine whether there was a load inside the pore size of the adsorbent. Before the analysis, the sample was first degassed at 200°C for 3 hours, and then the analysis and calculation were performed.
[0133] from Figure 4 It can be seen that: Figure 4 As shown in (a) and (b), the isotherm of the blank sample of aluminum oxide is type IV, and the isotherm of the carrier after loading is also type IV. At the same time, its hysteresis line is type H3 defined by I UPAC, indicating that this is a fracture pore material. The isotherm changes significantly between 0.4 and 1.0, which is related to the capillary condensation of densely packed nanoparticles in the uneven mesopores, which proves the existence of mesopores in the carrier. Figure 4 (c) and (d) show that the average pore size of the aluminum oxide carrier in the blank group is 5.45865nm, and the total pore volume is 0.4241cc / g. The average pore size of the granular manganese adsorbent carrier formed after impregnation coprecipitation and high-temperature calcination is reduced to 2.29870nm, and the total pore volume is reduced to 0.2363cc / g. Both the pore size and pore volume are reduced, which indicates that the lithium manganate adsorbent is indeed loaded into the carrier.
[0134] Figure 5 This is a FTI R diagram of the granular manganese-based lithium ion adsorbent of Example 1 of the present invention: This experiment uses a Fourier transform infrared absorption spectrometer (Thermo Nico let IS5, USA) to determine the Li 4 Mn 5 O 12 Whether there is spinel structure in the product. This characterization uses a small amount of sample and adsorbent in a ratio of 1:100 (i.e. 0.002g adsorbent and 0.2g sample), and 0.1g sample is pressed into a tablet using a tablet press, with a scanning range of 400-4000cm -1 .
[0135] from Figure 5 It can be seen that when the raw material ratio is 1.3:1 and the lithium-manganese ratio is 0.802, combined with Figure 3-5 Fourier transform infrared spectroscopy can analyze at 500cm -1 -650cm -1 The two absorption bands at are caused by Li-Mn-O spinel crystals (Mn(IV)O 6 )4+ -O and Mn 3+ -O antisymmetric stretching vibration, indicating that the sample is a spinel structure. This sample has a peak at 617 cm -1 and 514cm -1 There are two strong absorption bands, proving that the structure is a spinel structure.
[0136] Finally, it should be noted that the terms "comprises," "includes," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements that are inherent to such process, method, article, or apparatus.
[0137] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0138] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a granular manganese-based lithium ion adsorbent, characterized in that: The preparation method comprises: Dissolving a lithium salt and a manganese salt in water to obtain a lithium-manganese solution, and adding a carrier molecular sieve to the lithium-manganese solution to obtain a mixed solution; Adding a precipitant and a complexing agent to the mixed solution, stirring and reacting for a certain period of time to obtain a reaction solution; The reaction solution is aged, and then solid-liquid separation is performed, and the obtained precipitate is dried to obtain a coprecipitation carrier; The coprecipitated carrier is calcined at high temperature to obtain a manganese-based lithium ion adsorbent.
2. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 1, characterized in that: The lithium salt includes lithium sulfate monohydrate, the manganese salt includes manganese sulfate monohydrate, the molar ratio of the lithium salt to the manganese salt is (1-1.5):1, and the total concentration of the lithium manganese solution is 1.3-1.7 mol / L.
3. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 1 or 2, characterized in that: The carrier molecular sieve includes any one of activated alumina, 3A potassium molecular sieve, 4A sodium molecular sieve, 5A calcium molecular sieve and 13X sodium molecular sieve. The carrier molecular sieve is spherical in shape and has a particle size of 1 to 2 mm.
4. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 1 or 2, characterized in that: The step of adding a carrier molecular sieve to the lithium manganese solution to obtain a mixed solution specifically comprises: At 70-100° C., immersing the carrier molecular sieve in the lithium manganese solution for 20-30 minutes to obtain a mixed solution; Wherein, the ratio of the mass of the carrier molecular sieve to the volume of the lithium manganese solution is 6g:25ml.
5. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 1, characterized in that: The step of adding a precipitant and a complexing agent to the mixed solution and stirring the mixture for a certain period of time to obtain a reaction solution specifically comprises: Add the precipitant and the complexing agent to the mixed solution at 70-100° C. at a rate of 5-10 rpm, stirring during the addition process, and continue stirring for 50-60 minutes after the addition is completed to obtain a reaction solution.
6. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 5, characterized in that: The precipitant comprises a sodium carbonate solution, wherein the molar ratio of the sodium carbonate solution to the lithium manganese solution reaction substance is 1:(0.5-2); The complexing agent is ammonia water, the concentration of the ammonia water is 1-5 mol / L, and the volume ratio of the ammonia water to the lithium manganese solution is 1:
1.
7. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 1, characterized in that: The reaction solution is aged, solid-liquid separation is performed, and the obtained precipitate is dried to obtain a coprecipitation carrier, which specifically includes: The reaction solution is aged at 75-95° C. for 1-4 hours, and then solid-liquid separation is performed. The obtained precipitate is dried at 80-90° C. to obtain a coprecipitation carrier.
8. The method for preparing a granular manganese-based lithium ion adsorbent according to claim 1, characterized in that: The step of calcining the coprecipitated carrier at high temperature to obtain a manganese-based lithium ion adsorbent specifically comprises: The coprecipitated carrier is calcined at 400-600° C. for 8-12 hours, and then the powder is filtered off to obtain a manganese-based lithium ion adsorbent.
9. A granular manganese-based lithium ion adsorbent, characterized in that: The manganese-based lithium ion adsorbent is prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the granular manganese-based lithium ion adsorbent as claimed in claim 9 in extracting lithium from salt lake brine.
Citation Information
Patent Citations
Preparation method of manganese oxide ion sieve adsorbent and precursor thereof
CN104525094A
Lithium nickel cobalt manganese oxide precursor and preparation method thereof
CN107565124A
Preparation method of ceramic tube support loaded ion sieve
CN108160024A
Catalyst used for catalytic wet hydrogen peroxide oxidation method as well as preparation method and application thereof
CN109465009A
Recovery method of positive electrode material of waste ternary lithium ion battery
CN111252814A